Endoscopic Endonasal Transsphenoidal Pituitary Tumors Approach: Nuances of Neurosurgical Technique - Romero, Flavio Ramalho [UNESP]; Tagliarini, Jose Vicente [UNESP]; Nunes, Vania dos Santos [UNESP]; Zanini, Marco Antonio [UNESP] (Georg Thieme Verlag Kg, 2015)
Pituitary tumors are responsible for 7 to 17% of all intracranial lesions. Over the past decade, advances in endoscopic microsurgical techniques have resulted in an increasingly aggressive endonasal approach to tumors of the midline skull base. We present our series emphasizing technical nuances of endoscopic endonasal transsphenoidal approach to treat pituitary adenomas.
Keywords: pituitary tumors; transsphenoidal approach; skull base tumors